Comparison Between the Predicted and Experimental L-Glutamic Acid Production by Free Cells Of Corynebacterium Glutamicum x680 Using Mathematical Model (Dhaka University Journal of Biological Sciences, 2022)
The present investigation was undertaken to predict the amount of Lglutamic acid production by a mutant Corynebacterium glutamicum X680 using mathematical model emphasizing Bona and Moser (1997) hypotheses. This model was able to predict the experimental data with the minimum value of sum squares of weighted residues (sswr) 0.161. This model claimed that an increase in non-growth associated product formation coefficient led to maximum negative impact on L-glutamic acid production.Dhaka Univ. J. Biol. Sci. 31(1): 137-146, 2022 (January)